Testing the Cooperation of Autonomous Robotic Agents - Lill, Raimar; Saglietti, Francesca (Proceedings of the 9th International Conference on Software Engineering and Applications - ICSOFT-EA, 2014)
This article proposes an approach to testing the cooperative behaviour of autonomous software-based agents with safety-relevant tasks. It includes the definition of different model-based testing criteria based on the coverage of Coloured Petri Net entities as well as the automatic generation of appropriate test cases. The multi-objective optimization problem considered addresses both the maximization of interaction coverage and the minimization of the amount of test cases required. The approach developed for its solution makes use of genetic algorithms. The resulting automatic test case generation process is presented in this article together with the experiences gained by applying it to cooperating autonomous forklifts.
UnivIS-Import:2015-04-17:Pub.2014.tech.IMMD.lsinfs_1.testin_5
Keywords: Autonomous systems; Coloured petri nets; Genetic algorithms; Optimized test case generation; Structural testing